2020
DOI: 10.1038/s41598-020-66293-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of different alginate lyases for dissolving Pseudomonas aeruginosa biofilms

Abstract: Aggregates of Pseudomonas aeruginosa form a protective barrier against antibiotics and the immune system. These barriers, known as biofilms, are associated with several infectious diseases. One of the main components of these biofilms is alginate, a homo- and hetero-polysaccharide that consists of β-D-mannuronate (M) and α-L-guluronate (G) units. Alginate lyases degrade this sugar and have been proposed as biotherapeutic agents to dissolve P. aeruginosa biofilms. However, there are contradictory reports in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Núria et al observed the contradiction between different reports, and they tested five different alginate lyases in order to find the secrets behind the contradiction. According to their results, only enzymes with polyM/G activity are effective in dissolving biofilms and have a synergistic effect with ciprofloxacin antibiotic, while strict polyM or polyG specific alginate lyases show fewer activities and do not have the synergistic effect [92], which verifies that substrate specificity acts as a key factor in pharmaceutical applications, as described above. Here, this paper summarizes some online studies posted in recent years.…”
Section: Antibiotic Applicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Núria et al observed the contradiction between different reports, and they tested five different alginate lyases in order to find the secrets behind the contradiction. According to their results, only enzymes with polyM/G activity are effective in dissolving biofilms and have a synergistic effect with ciprofloxacin antibiotic, while strict polyM or polyG specific alginate lyases show fewer activities and do not have the synergistic effect [92], which verifies that substrate specificity acts as a key factor in pharmaceutical applications, as described above. Here, this paper summarizes some online studies posted in recent years.…”
Section: Antibiotic Applicationsmentioning
confidence: 79%
“…As a protective barrier, the thick biofilm is composed of several components [91]. Alginates are the major component of P. aeruginosa biofilm, which is responsible for surface adhesion and stabilization of biofilm to resist antibiotics [92,93]. Moreover, alginates can interrupt the phagocytosis of macrophages and neutrophils, limit the lymphocyte function, and induce inflammatory reactions to aggravate the lung infec-tion [91].…”
Section: Antibiotic Applicationsmentioning
confidence: 99%
“…Alginate is the salt of alginic acid, a bio-based polymer consisting of D-mannuronic and L-guluronic monomers extracted from brown marine algae (brown seaweeds) and some bacteria, such as Pseudomonas aeruginosa [ 93 , 94 ]. Alginate is nontoxic, non-antigenic, biocompatible, and biodegradable, and it has the capacity to form a hydrogel when applied in encapsulation.…”
Section: Biodegradable Food Packagingmentioning
confidence: 99%
“…CC-BY-NC 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 3, 2020. ; https://doi.org/10.1101/2020.07.24.220400 doi: bioRxiv preprint 4 [19]. KdgF was identified as the missing link in the microbial metabolism of uronate sugars from pectin and alginate|20] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%